Brain weight in sudden unexpected death in infancy: experience from a large single‐centre cohort. (7th July 2015) - Bamber, Andrew R.; Paine, Simon M. L.; Ridout, Deborah A.; Pryce, Jeremy W.; Jacques, Thomas S.; Sebire, Neil J.
Abstract : Aims: Published reports of brain weight in sudden infant death syndrome (SIDS) are contradictory, although several have concluded that brain weight is increased in SIDS compared with controls or reference data. This is important as, if brain weight is significantly different, it may be of diagnostic use or provide insights into the aetiology of SIDS. The aim of this study was to use a large series of well‐characterized sudden unexpected infant deaths from a single centre to provide definitive data regarding this issue. Methods: A retrospective review identified 1100 infants who had died suddenly and undergone a comprehensive autopsy at Great Ormond Street Hospital between 1996 and 2011. They were split into two groups: those in whom death could be explained and those whose deaths remained unexplained despite full investigation (SIDS/unexplained sudden unexpected death in infancy). Results: There were 1100 cases of whom 573 (52%) were unexplained and 527 (48%) explained. Multiple regression analysis, which adjusted for sex, age and post‐mortem interval, showed no difference in the ratio of brain weight : body weight between those infants dying of explained causes and those in whom no cause could be found. This finding remained true when restricting analysis to those with macroscopically normal brains. Conclusions: In this large series of infants dying of both explained and unexplained causes, brain weight, once corrected for body weight, did not vary consistently with the cause of death. Brain weight cannot be used as a diagnostic indicator of the cause of death or to inform hypothetical models of the pathogenesis of SIDS. Abstract : This large study of brain weight in cases of sudden infant death (SIDS) showed no difference in the ratio of brain to body weight compared with infants with an explained cause of death. Importantly this shows that brain weight cannot be used as a diagnostic indicator and that altered brain weight does not play a role in the pathogenesis of SIDs.